Emotional and cognitive aspects and quality of life in adolescents with disorders of sex development: case studies - Prade Hemesath, Tatiana; Rohrsetzer, Fernanda; Basso Brun, Juliana; Corrêa Costa, Eduardo; Guaragna-Filho, Guilherme; Unis Castan, Juliana (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2022)
This study describes emotional, cognitive and quality of life aspects of adolescents diagnosed with Disorders of Sex Development (DSD). It is a multiple case study that analyzed medical and psychological longitudinal records of 5 adolescents with DSD with female sex of rearing. The participants also performed a battery of emotional and cognitive tests. Similarities were found among the 5 participants, consistent with the adolescence stage and their conflicts. Body image concerns and desire for the development of secondary sexual characters were identified among them, as well as the maintenance of infantile behaviors as a way to avoid dealing with sexuality. Avoidance strategies are used to deal with anxiety arising from the process of transition into adult life.